THE IMPACT OF ORGANIZATIONAL LEADERSHIP AND JUSTICE ON ORGANIZATIONAL COMMITMENT - Mustika Wati Alfia Ningtyas; Ade Risna Sari; Riscki Elita Rosihana (Jurnal Ekonomi, 2023)
The purpose of this research is to examine the impact of leadership and organizational justice on organizational commitment. This study was carried out at a manufacturing company in Bandung, West Java. The study included 87 respondents who worked for a manufacturing company in Bandung. The sampling technique used in this study was non-probability sampling with the quota sampling method. Validity tests, reliability tests, model tests, and hypothesis testing were all performed in this study. Multiple linear regression is the analytical tool used. According to the findings of this study, leadership has a positive and significant impact on organizational commitment, while organizational justice has a positive and significant impact on organizational commitment. This study has both theoretical and practical implications.